2000
DOI: 10.1042/0264-6021:3530109
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 9 induces expression of three cytokine signal inhibitors: cytokine-inducible SH2-containing protein, suppressor of cytokine signalling (SOCS)-2 and SOCS-3, but only SOCS-3 overexpression suppresses interleukin 9 signalling

Abstract: Interleukin 9 (IL-9) is a cytokine preferentially produced by T helper type 2 lymphocytes and active on various cell types such as T-and B-lymphocytes, mast cells and haemopoietic progenitors. The IL-9 receptor (IL-9R) belongs to the haemopoietic receptor superfamily and its signal transduction involves mainly the Janus kinase\signal transducer and activator of transcription (JAK\STAT) pathway. Here we studied the implication of a novel family of suppressors of cytokine signalling (called CIS, for cytokine-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Nevertheless, upregulation of SOCS3 has been reported in CTCL and other malignancies in association with elevated JAK-STAT signalling [35], and in JAK2V617F positive myeloproliferative disorders together with STAT3 and STAT5B [36], consistent with our findings. Although, SOCS3 has been reported as a feedback target of JAK-STAT signalling via IL9 in a mouse T-cell lymphoma [37], our unpublished findings discount a similar mechanism in MAC-1/2A/2B (Ehrentraut et al, in preparation). In CTCL cells SOCS3 overexpression inhibits apoptosis induced by interferon-α [38].…”
Section: Discussionsupporting
confidence: 48%
“…Nevertheless, upregulation of SOCS3 has been reported in CTCL and other malignancies in association with elevated JAK-STAT signalling [35], and in JAK2V617F positive myeloproliferative disorders together with STAT3 and STAT5B [36], consistent with our findings. Although, SOCS3 has been reported as a feedback target of JAK-STAT signalling via IL9 in a mouse T-cell lymphoma [37], our unpublished findings discount a similar mechanism in MAC-1/2A/2B (Ehrentraut et al, in preparation). In CTCL cells SOCS3 overexpression inhibits apoptosis induced by interferon-α [38].…”
Section: Discussionsupporting
confidence: 48%
“…STAT3 is an important member of the signaling pathway activated in IL9-producing cells. It is recruited upon IL9 binding to its receptor via its SH2 domain (26) and is crucial for apoptosis inhibition (27). More recently, its expression in Sézary syndrome cells has been attributed to a positive feedback loop of IL21 (19).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptionally, STATs are responsible for upregulation of Socs3 transcripts following cytokine stimulation. (Auernhammer et al 1999; Gatto et al 2004; He et al 2003; Lejeune et al 2001; Naka et al 1997). Recently, it has been demonstrated that other factors such as Specificity protein 3 (Sp3), c-Fos, c-Jun and FOXO3a and coactivators CREB-binding protein (CBP) and p300 are also involved in the transcriptional activation of Socs3 in a cytokine- and cell type-dependent manner (Barclay et al 2007; Ehlting et al 2005; Qin et al 2007).…”
Section: Introductionmentioning
confidence: 99%